How Do Students Enact Group Reasoning Within Online Interprofessional Education? - Perversi, Paul; Burstein, Frada; Henderson, Zoe; Leech, Michelle; Schliephake, Kirsten; Kent, Fiona (Journal of Research in Interprofessional Practice and Education, 2022)
Background: The capability of an interprofessional healthcare team to reach a shared understanding through group reasoning is critical to good healthcare delivery. Models for clinical reasoning have proved useful but remain focused on individual cognitive processes. Whilst interprofessional education has steadily gained real-world traction, it is unclear how interprofessional student groups practice group reasoning when performing online tasks.Method: We analyzed the group reasoning processes with two teams of health professional students in an online interprofessional education task (n = 13). Two simulated interprofessional team meetings about a palliative case were audio recorded, transcribed, and deductively analyzed to determine the mechanisms of team deliberation using a previously published study of group reasoning.Results: The reasoning mechanisms outlined in a previous study (informationaccumulating, sense-making, and decision-making) were evident in an analysis of student group reasoning. In particular, students focused on sharing and agreeing on information, and to a lesser extent, recording information.Conclusion: Attention to the mechanisms of action may be useful to facilitate teaching interprofessional reasoning. Group reasoning may benefit from focusing student attention on these stages: 1) prioritizing and sequencing of options, methods for exposing agreement about shared information, shared understanding of the situation, and options; 2) techniques for critically evaluating information so that opportunities arise to identify when information may disrupt existing understandings; and 3) development of documentation tools to assist recording of the process.